Renewable portfolio standards in the USA: experience and compliance with targets - Bespalova, Olga Gennadyevna (Kansas State University, 2011)
Economic growth requires growth of energy consumption. In the second half of the twentieth century energy consumption began to outgrow its production and the United States. Consequently, we observe growing dependence of the U.S. economy on energy imports which is causing political and economic insecurity; increasing pollution and depletion of natural resources. One way to alleviate these problems is to encourage renewable electricity production. Because the electric power industry is the largest consumer of energy sources, including renewable energy, it has become one of the most frequent subjects of the regulatory policies and financial incentives aiming to stimulate renewable electricity production. One of the most promoted renewable energy policies in this industry is a renewable portfolio standard (RPS), which requires electric utilities and other retail electric providers to supply a specified amount of electricity sales from renewable energy sources. Currently 29 states and District of Columbia have the RPSs, while 7 states have goals; but only about two third of those with the RPS have certain targets to meet. To my best knowledge, there are no studies analyzing compliance with the RPSs targets or the role of penalty mechanism in the RPS design on meeting its goal. In my Master Thesis I estimate which states are in compliance with their individual RPSs goals and analyze which factors affect the probability of compliance, with the focus on the role of penalty size, and controlling for complimentary policies promoting renewable energy production. I use a fixed effects linear probability model and state level data. Results indicate that including a penalty in the RPS design significantly increases the probability that states will comply with their goals.
Keywords: Renewable Portfolio Standard (RPS); Renewable energy; Policy compliance; Penalty; Electric utilities; Electric power industry; Economics (0501); Environmental economics (0438); Public Policy and Social Welfare (0630)